Child Marriage, Reproductive Outcomes, and Service Utilization among Young Afghan Women: Findings from a Nationally Representative Survey in Afghanistan. Issue 3 (23rd June 2022) - Dadras, Omid; Khampaya, Tanaporn; Nakayama, Takeo
Abstract: This study explored the prevalence of child marriage and its association with reproductive outcomes and service utilization among young women in Afghanistan. We conducted a secondary analysis of data from the 2015 Afghanistan Demographic and Health Survey (DHS), focusing on women aged 20–24 years old based on the United Nations' recommendation on child marriage study. Multivariate logistic models examined the association between child marriage, reproductive outcomes, and service utilization. An estimated 52% of the Afghan women aged 20–24 married at ages less than 18 years. Poverty and illiteracy were associated with the higher likelihood of early marriage. There was a significant negative relationship between child marriage and history of rapid repeat childbirth, delivery by skilled personnel, and institutional delivery. In both adjusted and unadjusted models, women married at age ≤14 were more likely to experience terminated or unintended pregnancy, inadequate ANC, unmet need for family planning, and fistula; while, for those married at age 15–17 years, only terminated or unintended pregnancy remained significant. Strict international law enforcement and advocacy are needed in the current situation of Afghanistan to increase young women's education, promote their civil rights, and improve their autonomy and role in decision‐making concerning their fertility preferences and reproductive health.